Academic Supervision Management At Smk Negeri 1 Kaliwungu Semarang - Setiyono , Setiyono (2012)
This research has three purposes. They are describing the characteristic of supervision management structure at SMK Negeri 1 Kaliwungu Semarang; the characteristic of supervision activity at SMK Negeri 1 Kaliwungu Semarang; and the characteristic of supervision reported at SMK Negeri 1 Kaliwungu Semarang. This research is a qualitative research using ethnography design. The informants are the principal, vise principal, and teachers. Data collection method used in-depth interview, observation, and documentation. Analyzing data used interactive model which was started from (1) data reduction, (2) data display, and (3) conclusion. Data validity is triangulation of data source and method of collecting data.Based on the analyzed data, there are three findings. The first finding is the characteristic of supervision management structure at SMK Negeri 1 Kaliwungu Semarang consists of (1) the supervision management structure involves the principal, the vice principal of curriculum affair, and teacher, (2) each personnel has a task based on their basic tasks, (3) each personnel has a professional working relationship in an effort to succeed the academic supervision, and (4) the principal and the vice principal of curriculum affair cooperate in preparing the supervision program, schedule, and instrument in a coordination meeting. Secondly, the characteristic of supervision activity at SMK Negeri 1 Kaliwungu Semarang involves the activity carried out by the supervisor and teacher. In the preparation, the supervisor makes a supervision program, schedule, assessment instrument, and socialization of supervision. The preparation which is done by teacher is to prepare the instructional administration instrument. The supervision is done individually toward teacher with a classroom visit technique, classroom observation, and individual meeting. The supervisor conducts observation and assessment of several aspects that consists of (a) the completeness and appropriateness of the instructional administration instrument, (b) acquisition of instructional material, (c) acquisition or classroom management, (d) evaluation of learning, analysis, and follow-up. Thirdly, the characteristic of supervision reported at SMK Negeri 1 Kaliwungu Semarang includes the supervision reported consists of the overall implementation of supervision and feedback obtained from the whole set of supervision. The report is prepared by the supervisor and proposed to the leader, people supervised, and Department of Education and other relevant agencies to be taken as the consideration and further coaching.